دور القانون الانتخابي في اعادة تشكيل المشهد السياسي التونسي بعد 2011 (قراءة في نتائج الانتخابات التشريعية 2011، 2014) - لحواسنية, ياسمين (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
مثلت سنة 2011 تحول في الحياة السياسية، تم الانتقال من نظام الحزب الواحد الى تعددية سياسية حزبية فعلية وارتفع عدد الأحزاب السياسية في تونس وهذا عادي في مراحل الانتقال الديمقراطي، فأصبح الدستور التونسي 2014 يسمح للجميع بتشكيل الأحزاب من اقصى اليسار الى اقصى اليمين. فيما بعد اختار الشعب أن يكون التغيير تدريجي وأن يكون تغيير الموازين عبر صندوق الاقتراع (الانتخابات)، وسيكون تساؤلنا في هذه الورقة على فهم وتحليل اسباب تبني النظام السياسي التونسي قانون انتخابي مبني على افراز التنوع، وهل يساعد على افراز التنوع داخل المجتمع وينتج لنا ديمقراطية مستقرة وثابتة، وهل شجع هذا القانون الانتخابي الاحزاب الكبيرة وحد من هامش الاختلاف والتنوع داخل الاحزاب الصغيرة وهذا ما افرزته نتائج انتخابات المجلس التأسيسي 2011 والانتخابات التشريعية 2014. Abstract: The year 2011 represented a shift in political life. The transition from a one-party system to an actual political pluralism took place and the number of political parties in Tunisia increased, and this is normal in the stages of democratic transition. The Tunisian Constitution of 2014 allows everyone to form parties from the far left to the far right. Later, the people chose for the change to be gradual and for the change of scales to be through the ballot box (elections), and our question in this paper will be to understand and analyze the reasons why the Tunisian political system adopted an electoral law based on the production of diversity, and does it help to produce diversity within society and produce a stable democracy for us And it is fixed, and did this electoral law encourage large parties and limit the margin of difference and diversity within small parties, and this is what emerged from the results of the 2011 Constituent Assembly elections and the 2014 legislative elections.